2018
DOI: 10.1021/acs.analchem.7b04664
|View full text |Cite
|
Sign up to set email alerts
|

Total Capture, Convection-Limited Nanofluidic Immunoassays Exhibiting Nanoconfinement Effects

Abstract: Understanding nanoconfinement phenomena is necessary to develop nanofluidic technology platforms. One example of nanoconfinement phenomena is shifts in reaction equilibria toward reaction products in nanoconfined systems, which have been predicted theoretically and observed experimentally in DNA hybridization. Here we demonstrate a convection-limited nanofluidic immunoassay that achieves total capture of a target analyte and an apparent shift in the antibody-antigen reaction equilibrium due to nanoconfinement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…As many emerging nanosensing technologies require electric fields for biomolecule transport, separation, and detection, we determined whether nanoconfinement enhances molecular recognition under an applied electric field. We showed that the nanoconfinement effect on molecular recognition observed in in pressure‐driven and stationary‐flow systems also extends to electrophoretic separation systems with application of a high potential . However, in order for this technique to provide truly quantitative results, we must expand the parameter sweep of the model, investigate the impact of injection plug width variation on both experimental and simulated electropherograms, and examine the impact of second‐order reaction kinetics on the robustness of the numerical simulation technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As many emerging nanosensing technologies require electric fields for biomolecule transport, separation, and detection, we determined whether nanoconfinement enhances molecular recognition under an applied electric field. We showed that the nanoconfinement effect on molecular recognition observed in in pressure‐driven and stationary‐flow systems also extends to electrophoretic separation systems with application of a high potential . However, in order for this technique to provide truly quantitative results, we must expand the parameter sweep of the model, investigate the impact of injection plug width variation on both experimental and simulated electropherograms, and examine the impact of second‐order reaction kinetics on the robustness of the numerical simulation technique.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Galvin et al. observed confinement‐enhanced protein‐antibody association in a nanofluidic immunoassay .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the applications of UHD technology in biology, it was found that the addition of UHD of antibodies could cause the change in conformation of the target protein 40 . Also, some authors report that a substance may completely change its properties when tightly surrounded by certain structures 41,42 . As mentioned earlier, UHD process leads to formation of nanostructures and nanobubbles [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, contrary to polydimethylsiloxane (PDMS) based systems, the MEMS scaffold of the biosensors enables mechanical robustness, cost-effectiveness and capacity for large-scale manufacturing using well-controlled processes, which are all essential for a robust commercial product. Secondly, the fluidic system was developed based on a combination of micro-and nanoscale structures and uses only capillary forces instead of active actuation typically used Several academic works have demonstrated that nanofluidic systems can be used for rapid sensing of biomolecules [16][17][18][19][20] and have provided deep insights, supported by theoretical modelling, into the mechanisms by which biomolecular interactions are enhanced. While differences exist between these systems and the one presented here, notably regarding the fact that we have developed a homogeneous ('no-wash') system without pressuredriven actuation, it is important to point out that the analyte capture behavior observed is in line with the principle of nano-fluidics: efficient mass transfer and nanoconfinement as described in previous studies.…”
Section: Discussionmentioning
confidence: 99%